2011
DOI: 10.1590/s0102-33062011000100004
|View full text |Cite
|
Sign up to set email alerts
|

O estresse salino retarda o desenvolvimento morfofisiológico e a ativação de galactosidases de parede celular em caules de Vigna unguiculata

Abstract: ABSTRACT(Salt stress delays morphophysiological development and activation of cell wall galactosidases in Vigna unguiculata stems). In order to examine the participation of α-and β-galactosidases in the cell expansion of stems from cowpea seedlings submitted to salt stress during plant establishment as well as to analyze the eff ect of salt stress on the development of seedlings and enzymatic activities, Pitiúba cowpea seeds were sown in distilled water and in 100 mM NaCl. Th roughout seed germination and seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In that same species, Taarit et al (2010) observed a more dramatic (61%) decrease in plants exposed to 100 mM of NaCl. According to Sudério et al (2011), salinity affects plant growth by impeding cell elongation, a process mediated by alpha-and beta-galactosidases. Those authors demonstrated that high salinity levels reduce the activity of these enzymes, resulting in delayed stem growth in Vigna unguiculata seedlings.…”
Section: Resultsmentioning
confidence: 99%
“…In that same species, Taarit et al (2010) observed a more dramatic (61%) decrease in plants exposed to 100 mM of NaCl. According to Sudério et al (2011), salinity affects plant growth by impeding cell elongation, a process mediated by alpha-and beta-galactosidases. Those authors demonstrated that high salinity levels reduce the activity of these enzymes, resulting in delayed stem growth in Vigna unguiculata seedlings.…”
Section: Resultsmentioning
confidence: 99%
“…Salinity is important abiotic stress that affects production in several regions. It is aggravated by inadequate agricultural practices, especially those associated with irrigated agriculture (Sudério et al, 2011). Popcorn is grown in the second harvest and often with the use of irrigation.…”
Section: Introductionmentioning
confidence: 99%